PENGARUH PENERAPAN SISTEM INFORMASI AKUNTANSI, SISTEM PENGENDALIAN INTERNAL, DAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAP KUALITAS LAPORAN KEUANGAN SATUAN KERJA PERANGKAT DAERAH DI PEMERINTAH KOTA BANDA ACEH - Tawaqal, Irzal; Suparno, Suparno (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2017)
The purpose of this study is to examine the effect of the implementation of accounting information system, internal control system, and human resources competency to the quality of financial reports of working units (SKPD) in the Government of Banda Aceh. The population of this study are all the working units (SKPD) in the environment of Government of Banda Aceh (39 SKPD) with 2 respondents from every working unit for a total of 78 respondents. The data and informations needed for this research are collected by conducting field research. The data used in this research is primary data and data collection is done directly by using questionnaires. Data analysis method used is multiple linear regression. The results of the research are either simultaneously or partially support the hypothesis that the implementation of accounting information system, internal control system, and human resources competency affect the financial reports of working units (SKPD) in the Government of Banda Aceh